ANALISIS PERAN CHATBOT DALAM MENINGKATKAN PELAYANAN TERHADAP KONSUMEN DI E-COMMERCE - Mayla Humaira As-syiva; Muhammad Irwan Padli Nasution (Kohesi: Jurnal Sains dan Teknologi, 2023)
E-commerce, or electronic commerce, has drastically changed the business landscape by enabling businesses to sell products and services online. E-commerce encompasses the entire process of development, marketing, sales, delivery, payment and service, available 24 hours a day to customers, supported by the latest developments in AI (Artificial Intelligence). In the e-commerce landscape, chatbots have become irreplaceable virtual assistants for online stores, customers and business owners. In this case we will discuss the question of using chatbots, whether chatbots can answer all our questions and whether this service is useful for sellers. this research was conducted to answer questions that have been a question mark. This research uses the "literature study" method, which is a collection of facts and data in the form of theories or research as a basis for scientific work. Chatbots in e-commerce have some disadvantages, such as limited context understanding and dependence on accurate data. They may also be unable to respond to customer emotions, face language barriers, and be affected by privacy and security concerns. Despite these limitations, chatbots are still a valuable tool in e-commerce to improve customer service, operational efficiency, and the overall shopping experience